2017
DOI: 10.1111/jpn.12688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary polyphenol‐rich grape seed on growth performance, antioxidant capacity and ileal microflora in broiler chicks

Abstract: SummaryIn this study, we examined the effect of dietary supplementation with grape seed (GS) on the performance, carcass traits, plasma biochemistry, antioxidant status and ileal microflora in broilers. Experiment diets included a control diet (without additive) and three levels of GS powder (10, 20 and 40 g/kg of diet). Each diet was fed to a total of 300 one-day-old Cobb-500 chicks for 42 days. The addition of 20 g/kg of GS to the basal diet increased final body weight and body weight gain, improved the feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
103
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 24 publications
17
103
2
1
Order By: Relevance
“…However, guar bean contains some anti-nutritional factors like trypsin inhibitor and a galactomannan (guar gum) which affect feed conversion ratio and growth performance in broilers (Saxena and Pradhan, 1974). Diets supplemented with guar bean increases intestinal viscosity due to β-galactomannan leading to reduced nutrient digestibility especially in a day old chickens (Lee et al, 2003;Abu Hafsa et al, 2017). This increase in the intestinal viscosity has also a negative effect on passage rate resulting in poor feed intake (Yasar, 2003).…”
Section: Anti-nutritional Factors Of Guar Mealmentioning
confidence: 99%
“…However, guar bean contains some anti-nutritional factors like trypsin inhibitor and a galactomannan (guar gum) which affect feed conversion ratio and growth performance in broilers (Saxena and Pradhan, 1974). Diets supplemented with guar bean increases intestinal viscosity due to β-galactomannan leading to reduced nutrient digestibility especially in a day old chickens (Lee et al, 2003;Abu Hafsa et al, 2017). This increase in the intestinal viscosity has also a negative effect on passage rate resulting in poor feed intake (Yasar, 2003).…”
Section: Anti-nutritional Factors Of Guar Mealmentioning
confidence: 99%
“…However, GM contains anti‐nutritional factors such as galactomannan (residual guar gum; approximately 18–20% of DM), trypsin inhibitor and saponins, which affect nutrient digestibility, feed conversion ratio (FCR) and the growth performance of poultry. β ‐galactomannan of GM causes reduction in nutrient digestibility . Saponins present in guar meal also tend to form complex with protein, thus reducing the availability of protein.…”
Section: Introductionmentioning
confidence: 99%
“…-galactomannan of GM causes reduction in nutrient digestibility. 7,8 Saponins present in guar meal also tend to form complex with protein, thus reducing the availability of protein. Most studies have reported a reduction in performance of broilers fed a diet containing GM at 25 g kg −1 or higher levels.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier paper [19] dietary polyphenols did not significantly affect ASAT and ALAT, however, the researchers did not performed exact chemical identification of the bioactive components. In the composition used in our experiment, the coniferyl alcohol which possesses cytotoxicity [20] is high in level and can affect hepatic cells, as follows from ASAT and ALAT indicators in groups II and III.…”
Section: Introductionmentioning
confidence: 92%
“…Increased total antioxidant activity and SOD level in blood of broilers [24,25] were due to feed supplementation with gallic acid, an oak bark component. Increased blood catalase concentration also occurred in broiler chickens after use of grape seed powder as a source of polyphenolic substances in diet [19].…”
Section: Introductionmentioning
confidence: 95%